Evaluasi Kinerja Operasi Unit Koagulasi Flokulasi Dalam Sistem Instalasi Pengolahan Air Limbah - Endang Kusumawati; Rivaldo Rofie Fauzi Budiman; Rizky Setianto; Tifa Paramitha; Retno Dwi Jayanti (Jurnal Serambi Engineering, 2024)
The coagulation and flocculation processing units represent a series of processing units that employ physical and chemical methods. The objective of this research is to ascertain the impact of coagulant type on process parameters, including turbidity, TSS, and pH, within the coagulation-flocculation processing unit integrated within the WWTP system. This research employs the use of raw water in the form of an artificial wastewater with characteristics closely resembling those of domestic wastewater, with a particular focus on process parameters such as turbidity, total suspended solids (TSS), and pH. The coagulants employed in the coagulation process are polyaluminum chloride (PAC) and aluminum sulfate/alum (Al₂(SO₄)₃.18H₂O). The operation of the wastewater treatment plant (WWTP) is conducted with a coagulation stirring speed of 150 rpm, while flocculation is performed at 60 rpm. A jar test was conducted to ascertain the optimal dose and pH of the coagulant. The results demonstrated that the optimal dose of PAC was 50 ppm, with an optimal pH of 7. In contrast, the optimal dose of alum was 60 ppm, with an optimal pH of 8. The findings revealed that the dose obtained through the implementation of the jar test in the WWTP unit with a stirring speed of 150 rpm yielded the most effective PAC coagulant results, with a TSS value of 10.53 mg/L, turbidity of 4.01 NTU, and pH of 6.74, accompanied by a TSS efficiency value of 94.86%. The velocity gradient and residence time in the coagulation and flocculation units do not align with the specified design criteria. However, both the residence time and overflow rate in the sedimentation unit meet the prescribed design criteria.